Medical Cannabis in Palliative Psychiatry: Clinical Aspects of Affective Regulation and Legal Challenges - Val, Bellman,; Megan, Kiolbasa,; Manuel, Vasquez Franjul,; Vaishalee, Namdev,; Sarang, Choi,; Sasank, Isola, (International Journal of Innovative Research in Medical Science, 2021)
Millions of Americans use cannabis for medical purposes including but not limited to pain, nausea, mood changes and appetite stimulation. The use of cannabinoid in the palliative care setting is a relatively new trend. Given the fact that a patient receiving palliative care is not necessarily approaching death, the increasing need for palliative care as the American population ages, this literature review was compiled in order to examine the potential efficacy of cannabis in treating the mental health comorbidities of palliative care patients. We attempted to create the most comprehensive report on cannabinoid use in palliative psychiatry. It summarizes the most recently published science on cannabinoid use in palliative care patients and its impact on mood and anxiety symptoms. The mechanism of action of cannabinoids on their associated receptors was elucidated, as were the pharmacological roles that specific molecules in cannabinoids, like cannabidiolic acid and terpenes, play in cannabinoids’ overall efficacy. The legal impediments to widespread cannabis use were also explored. While the potential efficacy of cannabinoids has proven to be mixed, more research is necessary to ensure that a potentially vital resource in treating palliative care patients does not go underutilized.